Unprecedented mortality induced by extreme hot-drought in commercial planted Pinus spp stands is locally modulated by soil characteristics - Gatica, Mario Gabriel (2024)
Increased tree mortality associated with hotter-drought events has rarely been recorded in mature (>10 years old) commercial plantations. However, we report a recent (2021–2022 warm season) event of this kind that occurred across the Mesopotamian region of Argentina, South America. We aimed to elucidate the mortality timing, rate, and magnitude associated with environmental and stand characteristics at local scale to determine which conditions make these productive systems more vulnerable to extreme climatic events. Using Sentinel-2 satellite images and field-data we estimated the canopy mortality from November 2021 to October 2022, in Pinus spp afforestations (mainly P. taeda). We found that spatio-temporal heterogeneity in canopy mortality was associated with variation in soil and topographic characteristics, but not in stand age and size. We found that canopy mortality occurs at greater extent, earlier and faster in shallow soils (≤ 0.6 m), while the lowest mortality occurred at depressed and waterlogged areas. Intermediate levels of mortality were observed in deep soils (> 1 m), where relatively higher mortality occurred in areas with shallow water table signs, inhibiting deep root development. Our results suggest that sites allowing a deeper rooting system and/or where soil water availability is expected to be higher and long-lasting could represent areas with low-mortality risk for fast-growing pine plantations.